LANGUAGE ALTERNATION AS A RESOURCE IN THE CLASSROOM: A PRAGMATIC PERSPECTIVE ON KOREAN AMERICAN CHILDREN - Shin, Sarah J. (My University, 2000)
This paper reports findings from a study of bilingual language alternation by first grade Korean-American schoolchildren. Growing up as members of the Korean immigrant community in New York City, the children in this study all entered school with Korean as their mother tongue, and at the time of the investigation, alternated between Korean and English. English is acquired as a second language during childhood and becomes an important medium of communication both in school and in the community. This study examines how bilingual language alternation is used in the learning context of a mainstream classroom by a group of students who share the same mother tongue. The bilingual children were found to strategically employ language alternation to structure their discourse, to negotiate the language for the interaction, and to accommodate other participants' language competencies and preferences. Contrary to the assumption that code-switching is evidence of a linguistic deficit in bilingual speakers, the sequential analysis reveals that code-switching is used as an additional means to communicate the speaker's rhetorical meanings to others. Code-switching was deliberately used as a contextualization strategy. These findings have implications for creating a conducive learning environment for linguistic minority students in a mainstream classroom. (Contains 23 references.) (KFT)